1990
DOI: 10.1002/ana.410280503
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of neurological, metabolic, structural, and genetic evaluations in persons at risk for Huntington's disease

Abstract: We compared four diagnostic data sets for the assessment of individuals at risk for Huntington's disease. Fifty-four chorea-free persons were evaluated by neurological examination, positron emission tomography measurement of glucose metabolism, radiographic computerized tomographic measurement of caudate size, and genetic testing at the polymorphic DNA loci D4S10, D4S43, and D4S125. Twelve (22%) persons had abnormal caudate metabolism, 6 (11%) had subtle abnormalities of motor control, and 7 (13%) had computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(29 citation statements)
references
References 33 publications
3
25
1
Order By: Relevance
“…In addition, we demonstrated that there was no difference between baseline 2-DG labeling in WT and HD mice. Nevertheless, this issue could warrant additional investigation, especially in light of conflicting clinical studies concerning metabolic impairment in HD patients and presymptomatic HD gene carriers (Kuhl et al, 1982;Grafton et al, 1990;Feigin et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we demonstrated that there was no difference between baseline 2-DG labeling in WT and HD mice. Nevertheless, this issue could warrant additional investigation, especially in light of conflicting clinical studies concerning metabolic impairment in HD patients and presymptomatic HD gene carriers (Kuhl et al, 1982;Grafton et al, 1990;Feigin et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Terminal loss of markers may represent a response to perikaryal injury or dysfunction, or less likely, may indicate the primary site of neuronal damage in Huntington's disease. Richfield [4,7,8). Although the gene for HD was recently cloned, the pathogenesis of these progressive changes remains unknown [9}.…”
mentioning
confidence: 99%
“…These that huntingtin's normal function persists despite the presinclude apoptotic cascades, excitotoxicity, the possibility ence of a pathogenic glutamine repeat (11). Expression of huntingtin aggregate toxicity, and pernicious effects of levels for huntingtin are also critical, and mice expressing huntingtin protein-protein interactions, putatively via transglutaminase-catalyzed polyglutamine interactions that striatal hypometabolism precedes the bulk of tissue with glutamines, lysines, and polyamines in other proteins loss and occurs in asymptomatic at-risk subjects (44)(45)(46). (32)(33)(34).…”
Section: Introduction Discussionmentioning
confidence: 99%